Label information and consumer behaviour: Evidence on drinking milk sector - Andrea Marchini; Chiara Riganelli; Francesco Diotallevi; Bianca Polenzani (Agricultural and Food Economics, 2021)
The purpose of the research is to evaluate the impact of different kinds of information disclosures of milk labels, investigating the interest among consumers based on their consumption behaviours and characteristics. In this research, all the actions which lead to a healthiness, become expressions of a production process, among which consumers' food choices, purchase, preparation, and also self-production. Therefore, in the "health creation" production process, information and knowledge about food become "investments". In this context, label disclosures become a tangible expression of this kind of "investment". The research question is: what impact do purchase preferences and consumers' characteristics have on their interest towards the label information provided? Several information disclosures, both mandatory and voluntary, are investigated. Therefore, some choice attributes will be analysed as indicators of the consumer's behaviour in relation to his investment in food information. The methodology used for the analysis is an Ordered Logit. The analysis of the consumer's behaviour has been performed by transposing Ménard's analysis of firm corporate governance (Ménard, Agribus. 34:142-160, 2018) to the consumer as producer of welfare equity. The reduction of information asymmetry is a cost for the producer, and this research may be able to measure how much it would be convenient to invest in this reduction, based on the analysis of the consumer's behaviour toward his personal investment in food information acquisition.
Keywords: 330; Information; Labelling; Ordered logit; Quality disclosure